Desenvolvimento profissional de professores de Matemática : movimento de aprendizagem expansiva em um cenário pandêmico - Renata Rodrigues de matos oliveira (2023)
The objective of this thesis is to understand how the Professional Development (PD) of a group of mathematics teachers from a public school is characterized from an Activity Theory perspective. The development of this general objective enabled the production of the following specific objectives: i) to recognize the tasks that mathematics teachers perform at school, outside the classroom; ii) to identify the System-Activity of which mathematics teachers are part of; iii) to detect the conflicts, critical conflicts, dilemmas, and tensions experienced by mathematics teachers, throughout their demand for planning and pedagogical meeting; and iv) to understand how tensions, conflicts, critical conflicts, and contradictions influence, or not, the characterization of the Professional Development of this group of mathematics teachers. For the development of the investigation, it was based on the Activity Theory and a literature review was carried out on the concept of Teacher Professional Development. The research methodology, in the light of the Cultural-Historical Activity Theory, was based on the interventionist perspective. The intervention carried out was inspired and supported by the principles and tools of the Change Laboratory (VIRKKUNEN; NEWNHAM, 2015), with the aim of bringing about changes in the scope of work. To this end, seven sessions were held in which a pedagogue and four elementary school mathematics teachers from a public school in the city of Contagem, Minas Gerais, participated. The empirical material of the research is composed of: i) video recordings of the sessions and a meeting with pedagogues; ii) notes in a field notebook about the school's collective meetings and the observations about the sessions themselves; iii) recording responses to questions in a questionnaire; iv) and information recorded by school professionals in charts and tables. The analyses were carried out from the perspective of expansive learning under the lens of the Activity Theory (AT). Through this lens, it was possible to focus on the movements that took place in the System-Activity of External Teaching Work (ETW) that led to the reconceptualization of the object of the mathematics teachers Activity. Thus, the unit of analysis adopted was the ETW System, highlighting the conflicts, critical conflicts, dilemmas, tensions, and contradictions that manifested themselves in this Activity-System. This research was developed in a context of the Covid-19 pandemic, in which the adoption of remote teaching was boosted. This study shows that this teaching model brought a series of modifications to the mathematics teachers Activity. These modifications generated conflicts and tensions, and explained the existing contradictions in the ETW System. When facing the conflicts and tensions that were originated from the contradiction of adopting an individual work perspective in a work environment that imprinted a need for interaction with the community, the teachers provoked changes in their Activity- System. The changes that took place in the Activity-System made it possible for them to reconceptualize the object of the mathematics teachers Activity. With that, from the understanding of the reconceptualization of the Activity object, it was possible to understand theoretically that the Professional Development of mathematics teachers can be seen as an expansive learning process.